FEATURES OF THE SYSTEM OF COMMUNICATION IN THE ORGANIZATION OF PROBLEM EDUCATIONAL CLASSES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article discusses the features of the organization of problem-based learning in the educational process and the importance of the communicative system in problem-based learning.